MENGONSTRUKSI LANDASAN ILMU DALAM ISLAM: KAJIAN EPISTEMOLOGI WAHYU, AKAL, DAN INTUISI - Arifah Elwahdiyah; Amril M; Yenni Kurniawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Epistemology is the study of the sources, nature, and methods of acquiring knowledge. From an Islamic perspective, knowledge is acquired not only through reason and empirical experience, but also through revelation and intuition, which are related to the spiritual dimension of humankind. Understanding these sources of knowledge is crucial in building a foundation for knowledge within the Islamic intellectual tradition. This study aims to examine the construction of the foundation for knowledge in Islam through an epistemological perspective, examining revelation as a source of knowledge and the role of reason and intuition as instruments in understanding and developing knowledge. This study employed a qualitative method with library research. Data were obtained through documentation studies of various relevant literature and analyzed using descriptive-analytical methods. The results show that in Islamic epistemology, revelation serves as a divine source of truth and is the primary foundation for knowledge, while reason and intuition serve as instruments used by humans to understand, develop, and internalize that knowledge. The integration of these three forms a comprehensive and balanced Islamic epistemological system in building a foundation for knowledge.